The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.1177/2515690x221150527
|View full text |Cite
|
Sign up to set email alerts
|

Cananga odorata Aromatherapy Reduces Anxiety in Unexperienced Patients Hospitalized for Interventional Neuroradiology Procedures: A Randomized Control Trial

Abstract: The hospitalization and the unfamiliar experiences of patients in interventional radiology procedures cause a moderate to high levels of anxiety. This study was aimed to evaluate the anxiolytic effect of Cananga odorata essential oil (COE) aromatherapy in unexperienced patients hospitalized for interventional neuroradiology (INR) procedures. Forty-four patients admitted for their first INR procedure were randomly divided into COE and placebo control groups. COE or distilled water was dropped onto 2 pieces of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…(biberiye), Crocus sativus L. (safran) gibi uçucu yağların, müdahale gruplarında ya da kontrol, plasebo gruplarında kullanılan aromatik yağlar olduğu görülmüştür. [50][51][52][53][54][55][56][57][58][59][60][61][62][63][64][65][66][67] Aromaterapide kullanılan, anksiyolitik etkileri değerlendirilen diğer uçucu yağlarla yapılan çalışmalar Tablo 3'te verilmiştir.…”
Section: Papatya Uçucu Yaği Ve Anksi̇yeteunclassified
“…(biberiye), Crocus sativus L. (safran) gibi uçucu yağların, müdahale gruplarında ya da kontrol, plasebo gruplarında kullanılan aromatik yağlar olduğu görülmüştür. [50][51][52][53][54][55][56][57][58][59][60][61][62][63][64][65][66][67] Aromaterapide kullanılan, anksiyolitik etkileri değerlendirilen diğer uçucu yağlarla yapılan çalışmalar Tablo 3'te verilmiştir.…”
Section: Papatya Uçucu Yaği Ve Anksi̇yeteunclassified
“…There is a limited number of investigations concerning the insecticidal effect of ylang-ylang essential oil [227][228][229]. Applications studied on humans in clinical studies include local application [230], aromatherapy [231], and inhalation [232,233]. It appears that clinical studies mainly focused on the impact of ylangylang essential oils against psychiatric disorders.…”
Section: Psychological Effectsmentioning
confidence: 99%
“…Moreover, there are older studies with a small number of patients included, which indicated that ylang-ylang essential oil could increase calmness, reduce cognitive abilities [234], relax participants, and decrease blood pressure [232,235,236]. It can be concluded from these studies that ylang-ylang essential oil is likely to have pronounced calming and sedative effects [230][231][232]234].…”
Section: Psychological Effectsmentioning
confidence: 99%
See 2 more Smart Citations